2001
DOI: 10.1046/j.1365-2222.2001.01200.x
|View full text |Cite
|
Sign up to set email alerts
|

IgE binding to soluble and insoluble wheat flour proteins in atopic and non-atopic patients suffering from gastrointestinal symptoms after wheat ingestion

Abstract: For the atopic patients the positivity to skin prick test and CAP to wheat was in accordance with the immunoblotting results and a food allergy to wheat could be diagnosed. In these patients a major allergen was a 16-kDa band corresponding to members of the cereal alpha-amylase/trypsin inhibitors protein family, the major allergens involved in baker's asthma. In the non-atopic patients the positive immunoblotting results contrasted with the responses of the allergologic tests, indicating that the allergenic wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 34 publications
2
62
0
1
Order By: Relevance
“…It is hypothesized that mucosal immune activation by FAs may contribute to the development of food allergy and IBS [9,11,13,[15][16][17]21,25] . Clinically, the role of food-intolerance-induced symptoms in IBS frequently contrasts with that in food allergy [20,[22][23][24][25]29,[37][38][39][40][41][42] , and dietary elimination may be associated with symptom improvement [31] . However, the interaction of food with the gastrointestinal system is not completely understood [13,17,20,22,23,25,29,[33][34][35][36][37]39] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesized that mucosal immune activation by FAs may contribute to the development of food allergy and IBS [9,11,13,[15][16][17]21,25] . Clinically, the role of food-intolerance-induced symptoms in IBS frequently contrasts with that in food allergy [20,[22][23][24][25]29,[37][38][39][40][41][42] , and dietary elimination may be associated with symptom improvement [31] . However, the interaction of food with the gastrointestinal system is not completely understood [13,17,20,22,23,25,29,[33][34][35][36][37]39] .…”
Section: Discussionmentioning
confidence: 99%
“…The increase in intestinal permeability could conceivably activate the release of neurotransmitters that stimulate afferent neurons [13] . Scientific evidence of the functional interface between the immune and sensory motor systems of the gut and respiratory systems has been reported [34,35,39] . Recent studies have reported that the prevalence of asthma and respiratory bronchial hyper-responsiveness are more common in IBS patients than in controls, and have suggested that at least a subset of IBS patients may have a systemic immunological disorder [27,28] .…”
Section: Discussionmentioning
confidence: 99%
“…and high m.w. glutenin subunits (LMW-GSs and HMW-GSs, respectively) (9, 10), a-amylase inhibitor subunits (11)(12)(13)(14)(15), and lipid transfer protein (10,16), the panel of wheat allergens is still incomplete (17).…”
mentioning
confidence: 99%
“…Hypersensitivity reactions after wheat ingestion have been reported by several authors (James et al 1997;Mittag et al 2004). Ingestion of foods containing wheat and other related cereals can induce gastrointestinal (GI) symptoms by either immunological or non-immunological mechanisms (Simonato et al, 2001). Figure 4 shows the kinetics of pepsin hydrolysis of both wheat protein extracts.…”
Section: Resultsmentioning
confidence: 95%